Measuring digital era impact on brand interaction among young emerging consumers: a case study of colombian consumers - Cabrera Rios, Nelson (Pontificia Universidad Católica del Perú, 2017)
Traditional marketing employs the brand funnel metaphor to explain the purchasing process of customers, in order to better aim its efforts towards influencing their decisions. Said funnel is based around five stages: awareness, consideration, buy, loyalty and engagement. However, there is a new reality of hyper-connected digital consumers, which have at their disposition hundreds of means of communication, changing their relationship with brands and putting the significance and accuracy of the brand funnel into question. This is especially prevalent among young emerging consumers. The current study measured and analyzes the impact of the digital era on brand interaction among young emerging consumers in the Colombian case, thus focusing on emerging markets, while analyzing brands in both mass consumption and durable goods markets. A structural equation model (SEM) was created to estimate how these new technologies affected the relationships between the stages of the brand funnel, while controlling factors such as media drivers, age and socioeconomic stratum. It was found that social interactions affect consumers’ confidence and hold a significant sway on purchasing decisions, especially among young consumers. Significantly, the importance of social network recommendations on purchasing decisions among young demographics in emerging markets was validated through the results of the current study
Keywords: Mercadeo en Internet--Colombia; Redes sociales; Comportamiento del consumidor; Investigación cuantitativa; https://purl.org/pe-repo/ocde/ford#5.02.04